The medicinal mushroom Auricularia auricula-judae (Bull.) extract has antioxidant activity and promotes procollagen biosynthesis in HaCaT cells. Issue 22 (17th November 2019) - Choi, Young-Ji; Park, In-Sun; Kim, Mi-Hee; Kwon, Bora; Choo, Young-Moo; Jeong, Seung-Il; Yu, Kang-Yeol; Choe, Chung Hyeon; Kim, Jiyoung
Abstract: In this study, Auricularia auricula - judae (Bull.) extract (AAE) had potent antioxidant activity in vitro and promoted the biosynthesis of procollagen, a precursor of collagen in HaCaT cells. In addition, the expression of HAS - 3 (hyaluronic acid synthase), which is a moisturizing factor, was increased in HaCaT cells in response to AAE. Therefore, this work suggests that AAE has the potential to exhibit antioxidant activity and promote procollagen biosynthesis in HaCaT cells. Abstract :